Thermal Environments and Visitor Attendance in Zoological Parks: Observations in A Humid Continental Climate - David R. Perkins (Journal of Tourismology)
This paper reviews associations between weather and visitor attendance at two climatically similar zoological parks. This is achieved by examining weather, climate, and attendance data at the Indianapolis and St. Louis zoological parks over a period of approximately one decade. The methodological approach utilizes tourism climatology as the foundation for information gathering, display, and analysis of results. Peak days of attendance at both zoos coincide with ‘warm’ and ‘slightly’ warm days. Regarding the lowest attendances, visitors at both locations appear to display more aversion to cold thermal stress conditions than hot thermal stress conditions, however visitors at St. Louis Zoo appear to be more averse to cold conditions. Discussions regarding how social calendars and admission pricing may interact with this relationship are introduced.